Neonatal seizures: diagnostic updates based on new definition and classification - Eun-Hee Kim; Jeongmin Shin; Byoung Kook Lee (The Korean Pediatric Society, 2022)
Neonatal seizures are the most common neurological symptoms caused by various etiologies in the neonatal period, but their diagnosis and treatment are challenging because their pathophysiology and electroclinical manifestations differ from those of patients in older age groups. Many seizures present as electrographic-only events without clinical signs or as obscure clinical manifestations that are difficult to distinguish from other neonatal behaviors. Accordingly, a new definition and classification of neonatal seizures was recently proposed by the International League Against Epilepsy Task Force on neonatal seizures, highlighting the role of electroencephalography in diagnosing and treating neonatal seizures. Neonatal seizures are defined as electrographic events with sudden, paroxysmal, and abnormal alteration of activity and divided into electroclinical seizures and electrographic-only seizures according to their clinical signs, thus excluding clinical events without an electrographic correlation. Seizure types are described by their predominant clinical features and divided into motor (automatisms, clonic, epileptic spasms, myoclonic, tonic, and sequential), nonmotor (autonomic and behavioral arrest), and unclassified. Although many neonatal seizures are acute reactive events caused by hypoxic-ischemic encephalopathy or vascular insults, structural, genetic, or metabolic etiologies of neonatal-onset epilepsy should also be thoroughly evaluated to determine their appropriate management.